Authorized Failure: How is Company Status? - Lasnita, Fiany Alifia; Utama, Muhamad Adji Rahardian (Indonesian Journal of Advocacy and Legal Services, 2020)
The sense of the limited liability company is a legal entity to be able to run a business that has a capital consisting of a share, which its owners have lots of stock. Because it is composed of capital over shares that can be traded, and changes to the ownership of the company can be done without the need for a dissolution of a company. Limited liability company is a business entity and the magnitude of the capital company which are poured in a basic budget. The wealth of the company separate from the personal wealth of the owners of the company so that it can have its own treasures. Each person can have more than one stock which can be a proof of ownership of a company. The owner of the stock itself has a limited liability, i.e. as much as their shares. In the establishment of limited liability company also required permission and also some important documents that should be owned by a limited liability company to be its foundation.